Disseminated Exfoliative Dermatitis Associated with All-Transretinoic Acid in the Treatment of Acute Promyelocytic Leukemia - Yonal Ipek; Dogru Hulya; Aktan Melih (Case Reports in Medicine)
Acute promyelocytic leukemia (APL) is a biologically and clinically separate type of acute myeloid leukemia characterized by a translocation involving the retinoic acid receptor-alpha (RARa) locus on chromosome 17, the great majority of which is t(15; 17)(q24.1; q21.1) (Collins (1998), Melnick and Licht (1999), and Grimwade (1999)). Retinoic acid is a critical ligand in the differentiation pathway of multiple tissues, mediated through binding to an RAR. All-trans retinoic acid (ATRA) is a subgroup of the retinoid family, which induces complete remission (CR) in APL by causing differentiation and apoptosis in immature malignant promyelocytes rather than inducing cell death by cytotoxicity (Warrell et al. (1993), Liu et al. (2000), and Cassinat et al. (2001)). ATRA-associated toxicity consisting of headache, fever, weakness, fatigue, dry skin, dermatitis, gastrointestinal disorders, and hypertriglyceridemia has been shown to be mild (Kurzrock et al. (1993)). Herein, we describe a patient with APL that developed an erythematous reaction of the whole body followed by desquamation and exfoliation during ATRA therapy.